Internalisasi Nilai-Nilai Karakter pada Anak Usia Dini di Era Pandemi Covid-19 - Nugroho, Puspo; Inayah, Faiq Zahrotul; Musdalifah, Novi Linda (PIAUD Universitas Islam Negeri Sunan Kudus, 2021)
This study aims to find out how the teacher’s efforts to internalize character values in early childhood during the covid-19 pandemic at Masyithoh Cebolek Margoyoso Pati Kindergarten and the problems they face. In its implementation, it uses a qualitative case study approach with data collection techniques through observation, interviews, and documentation. Research subjects include teachers and literature searches. The results showed that the first; character values instilled in early childhood consist of 18 character values as referred to by the Ministry of Education and Culture, second; teachers’ efforts to internalize character values during the Covid-19 pandemic through several ways including a) continuous habituation, b) application of blended learning systems, c) application of multiple methods in every learning and d) strengthening of parenting parents offline and online. Third; the emergence of problems in the implementation of internalization such as the lack of responsiveness of parents in assisting learning, technological stuttering, inadequate network availability, loss of children’s independence due to excessive parental assistance, limited parental assistance time. All of these problems are dealt with by forming a communication platform in the form of a parent association as a medium for sharing, communicating, and sharing information and experiences.